Knowledge, attitude and practice of nurses in administering oral medication at Medical Ward, Universiti Kebangsaan Malaysia Medical Centre - Raja Lexshimi RG,; Fazlinee Daud,; Syed Zulkifli SZ, (Penerbit UKM, 2009)
Drug administration is an integral part of nurses role in nursing practice. In relation to their diverse roles, nurses are required to have adequate knowledge and good practice. The purpose of this study is to examine the level of knowledge, attitude and practice of nurses in the medical wards administering oral medication and to assess whether nurse’s knowledge, attitude and practice is associated with working experience and professional education (post basic training). A cross-sectional study was conducted on forty (40) nurses working in the Medical wards in Universiti Kebangsaan Malaysia Medical Centre (UKMMC). Questionnaires were used to measure the level of knowledge and attitude of nurses and a direct observation technique with checklist to record the practice of nurses. The mean score for knowledge (13.8), attitude (16.4) and practice (10.7) were all within average distribution. No significant difference was found between knowledge and practice of nurses with working experience and post basic training. However, the influence of working experience on attitude of nurses in serving oral medication was found to be significant (p= 0.045). Nurses in medical ward, Universiti Kebangsaan Malaysia Medical Centre, were found to possess an average level of knowledge and attitude in administering oral medication. In addition, this study suggest that work experience of nurses has no influence on knowledge gain and good practice in administering oral medication.